Primary School Student Learning Motivation in Online Learning During the Covid-19 Pandemic - Ardiyanto, Eko; Muharam, Agus (International Conference on Elementary Education, 2021)
This article aims to explain the objective conditions of students' learning motivation in online learning in covid-19 pandemic conditions. This research uses a quantitative approach to survey methods. The subjects in this study were 95 grade, 5 students, at SDN 114 Bojongkoneng Cibeunying who learned to use online methods. The data collection techniques used in this study use survey techniques with a Likert scale. The research instrument used is a learning motivation questionnaire specially designed using Google Forms. The number of statements used is 20 motivational statements learned. The data analysis technique used in this study is to calculate the percentage of each indicator, then interpret the score of the data presentation and analyze each indicator in depth. The results showed that students' motivational percentage scores in online learning in grade 5 of SDN 114 Bojongkoneng Cibeunying amounted to 80.27% in the excellent category. This research is expected to be an evaluation material, especially for education policymakers in organizing online learning in elementary schools related to motivation, and is expected to be a study material for other researchers to develop research on the motivation of learning students in online learning during the pandemic in elementary school.